Les jeunes dans la rébellion du nord de la Côte d’Ivoire : les raisons de la mobilisation - Fofana, Moussa (Afrika Focus, 2011)
The armed conflict that started on 19th September 2002 in Côte d’Ivoire has led to the temporary de facto separation of the country into two entities. The rebels of the “Forces Nouvelles” have control of the north while the “Loyalist” camp has retained control of the south. The “Forces Nouvelles” have justfied their actions against the regime by denouncing the social injustice and discrimination that Northerners are said to endure. Also substantial numbers of youths from the North joined the rebel force. This study is based on in depth interviews conducted with 22 of such youths and their leaders. It gives a thorough account of their reasons for enlistment and their perceptions of the conflict. The reasons can be categorized as follows: in the first instance, the fighters claim their right to be fully recognized as Ivorian citizens and to be given official ID cards. Many also express an unwillingness to tolerate the abuses the national security forces have perpetrated against them, alongside their desire for revenge; their search for protection or, in a more self-interested way, their desire to pursue a military career. The study also highlights the influence that parents and peers from the neighbourhood can have on the decision to enlist and specific Northern “national” discourse discriminated by the rebellion. In the end, far from carrying secessionist claims, the discourses we have recorded express frustration at the continuing exclusion of Northerners from participation in the state. Beyond individual cases, we hypothesize that rebelling has been a way for the youths to re-negotiate their sense of belonging to and in the Nation. Key words: Côte d’Ivoire, Forces Nouvelles, rébellion, political violence, violent engagement